A rare case of cemento-osseous dysplasia arising from a dislocated impacted tooth in the maxillary sinus. Issue 2 (March 2019) - Yoshizumi, Junko; Wada, Hiroko; Shimizu, Mayumi; Horinouchi, Yasufumi; Kiyoshima, Tamotsu; Ikebe, Tetsuro; Hiraki, Akimitsu
Abstract: Fibro-osseous and osteochondromatous lesions are non-neoplastic lesions containing metaplastic bone and/or cementum. The World Health Organization classification (4 th edition, 2017) has categorized these lesions into subgroups: ossifying fibroma, familial gigantiform cementoma, fibrous dysplasia, cemento-osseous dysplasia and osteochondroma. We report a highly unusual case of cemento-osseous dysplasia in a 32-year-old male complaining of discomfort of the left cheek. The radiographic examination revealed that a spherical radiopaque lesion, which involved a tooth, was located in the left maxillary sinus. A definitive diagnosis could not be made based only on the radiographic and clinical findings. An excisional biopsy was performed by opening the left maxillary sinus under the general anaesthesia. Histopathological examination revealed that the lesion consists of fibrous tissue, woven bone and masses of cementum-like material associated with a dislocated tooth. Together with the radiographic, clinical and histopathological findings, the lesion was diagnosed as cemento-osseous dysplasia. Differential diagnosis between fibro-osseous lesions and tumor is critical; the present case highlights the importance of correlating clinical, radiological and histopathological findings in order to correctly diagnose and manage oral and maxillofacial lesions.